The linkage between opioid treatment programs and recovery community centers: results of a survey of OTP directors - Hoeppner, Bettina B.; Williamson, Alivia C.; Nicoll, Cora; Finley-Abboud, Diadora; Futter, Allison; Joseph, Judeline; Burton, Angela; Hickman, Drew; Bradley, Anita; Pullen, Felecia; Johnson, Andre; Hoeppner, Susanne S. (Frontiers in Public Health, 2025)
ObjectiveMedications for opioid use disorder (MOUDs) are regarded as the gold-standard treatment for opioid use disorder in the United States and are widely used in other countries. In the US, the country most impacted by the opioid epidemic, opioid treatment programs (OTPs) are the primary avenue of accessing MOUDs. US federal guidance states that treatment providers should connect patients with recovery community centers (RCCs), if available. RCCs have emerged relatively recently. It is not clear to what extent OTP directors are aware of RCCs. Close collaboration is needed especially in Black communities, as Black Americans face significant disparities in opioid-involved overdoses and deaths.MethodsWe conducted an online survey and interviews of directors of OTPs located near RCCs serving Black communities (operationally defined as located in a ZIP code where ≥25% of residents are Black, as per US Census data). For each such RCC (n = 47 nationwide), we used the SAMHSA Treatment Locator to identify and record data (e.g., types of opioid treatment, treatment approaches, in-house recovery support services) about the three nearest OTPs. The survey asked about the OTP’s referral practices to mutual help organizations (MHOs) and recovery support services, knowledge of and interactions with the nearby RCC, and attitudes toward referral to RCCs, including potential barriers to referral. Interviews discussed barriers and potential solutions.ResultsFifteen OTPs completed surveys (32% of targeted locations), and five directors completed interviews. OTPs participating in the survey were comparable to non-participating OTPs on Locator-reported variables. OTPs provided referral to 12-step MHOs (100%); fewer (80%) were familiar with RCCs, provided referral to RCCs (67%), or knew the nearby RCC (40%). OTP directors (100%) reported that routine referral from the OTP to RCCs makes sense and is valuable. Most common barriers were lack of knowledge of RCCs, worries that RCCs may not be supportive of MOUD use, and lack of personnel to build and maintain connections with RCCs.ConclusionEfforts are needed to increase knowledge about RCCs among OTP leadership and staff. Needed knowledge includes general knowledge (i.e., RCCs are welcoming toward MOUDs; RCCs offer complementing support) and logistical information (e.g., RCC opening hours, transportation, that services are free).